2015
DOI: 10.1186/s12957-015-0525-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analyses of trends in pancreatic surgery: indications, operative techniques, and postoperative outcome of 1,120 pancreatic resections

Abstract: BackgroundHospital volume, surgeons’ experience, and adequate management of complications are factors that contribute to a better outcome after pancreatic resections. The aim of our study was to analyze trends in indications, surgical techniques, and postoperative outcome in more than 1,100 pancreatic resections.MethodsOne thousand one hundred twenty pancreatic resections were performed since 1994. The vast majority of operations were performed by three surgeons. Perioperative data were documented in a pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
2
6
0
Order By: Relevance
“…The rate and type of observed complications in the present study were comparable to average long‐term observational studies . Similar to earlier reports, in a substantial number of patients after bile duct stenting, bile was infected and bacterial strains were not restricted to gut‐associated strains .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The rate and type of observed complications in the present study were comparable to average long‐term observational studies . Similar to earlier reports, in a substantial number of patients after bile duct stenting, bile was infected and bacterial strains were not restricted to gut‐associated strains .…”
Section: Discussionsupporting
confidence: 90%
“…24 The rate and type of observed complications in the present study were comparable to average long-term observational studies. 25 Similar to earlier reports, in a substantial number of patients after bile duct stenting, bile was infected and bacterial strains were not restricted to gut-associated strains. 26 These bacterial contaminations not only increased the risk for cholangitis, but apparently even increased perioperative complications such as postoperative pancreatic fistulas, the main factor for perioperative morbidity after pancreatoduodenectomy.…”
Section: Discussionsupporting
confidence: 83%
“…Pancreatic cancer remains one of the leading causes of cancer death worldwide (1). Surgical resection is a mainstay of many gastrointestinal (GI) cancers, but pancreatic surgery has significant morbidity and mortality (2). Much improvement has been achieved in minimizing mortality but pancreatic surgery remains one of the most morbid procedures (2).…”
Section: Introductionmentioning
confidence: 99%
“…As safety profiles for PD have improved and the potential for long term disease free survival become more well established, pancreaticoduodenectomy with segmental resection of the porto-mesenteric venous system (PDVR) has become increasingly utilized in attempt to achieve margin-negative resection in patients with these tumors. 3,4 Many studies have examined the safety and efficacy of PDVR but the results of these studies have been mixed. Several single institutional studies as well as multicenter studies have found comparable postoperative morbidity rates for patients undergoing PDVR compared to PD alone.…”
Section: Introductionmentioning
confidence: 99%